Diseño e implementación de una escuela para padres y madres de familia en Liceo Juan XXIII del cantón Huaquillas en el año 2010. - Brito Encalada, Laura del Carmen (2011)
In our country the collaboration of parents with school has been rare, we can say there is no tradition in this regard. Therefore it should aim to achieve greater cooperation between school and family.